Free fatty acids regulating action of Capparis decidua fruit on dyslipidemia in rats - Avijit Saha; Sangeeta Ghosh; Alok K. Hazra; Sandip Ghosh; Tapas Kumar Sur (Universitas Ahmad Dahlan, 2022)
Capparis decidua belongs to family Capparidaceae in wastelands of India. The study aim was to determine the role of C. decidua fruits on the free fatty acids (FFA) profile in fat-rich diet (FRD) dyslipidemic rats. The methanolic extract of edible fruit of C. decidua (CD) was given orally to obese dyslipidemic rats at the dose of 125 mg/kg and 250 mg/kg for consecutive 28 days. CD treatment in FRD rats significantly restricts the body weight gains. Blood lipid profile was altered dose dependently and significantly after 4-week treatment with CD to FRD. rats. It significantly (p<0.05) enhanced serum FFA especially, g-linolinate, a-linolinate, arachidonate, ecosapentaenoate, docosapentaenoate and docosahexaenoate. Moreover, w3-PUFA content was also enhanced (50.3% and 78.8%) in the serum of CD treated animals, whereas MUFA was lowered (31.1% and 40%). Therefore, Capparis decidua fruit has a promising role on dyslipidemia and obesity and has the capabilities to regulate beneficial free fatty acids.